Application of Distributed Databases for Information Systems Fertilizer Management - Ali, A H; Nugraha, R A (IOP conference series. Materials Science and Engineering, 2019)
The purpose of this study is to identify and build applications that will integrate two databases and testing system by using black-box. The stages of the research method were systematic observation, data collection, system design, manufacture, and final system testing. The results of this study are the implementation of distributed database-based fertilizer buying and selling transactions that are used as online fertilizer stock reporting from retailers to distributors. The conclusion of this study is by utilizing the Internet with the proposed system (distributed database application) than providing an alternative in the process of fertilizer transactions by distributor and fertilizer stores.